Preparation method of anti-fouling super-hydrophobic membrane and application thereof in treating wastewater

CN118161987BActive Publication Date: 2026-10-20ANHUI POLYTECHNIC UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410433563.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-11
Publication Date
2026-10-20
Estimated Expiration
2044-04-11

AI Technical Summary

Technical Problem

但是在具有均匀纤维结构静电纺纤维膜表面创建微纹理结构,同时在纤维表面引入纳米级粗糙度,需要精确控制溶剂和非溶剂的比例,以及需要在静电纺丝过程中严格控制温度和湿度,这为制备过程的简便性带来了挑战

Benefits of technology

[0026]在现有技术中,制备PVDF-HFP静电纺丝膜也有报道使用NMP作为溶剂,例如专利申请CN 105390646 A公开了通过静电纺丝法制备复合膜的方法,溶剂可以是NMP,含氟树脂可以是PVDF-HFP,但是该专利制备的是均匀纤维结构的纤维膜,该制备方法除了使用NMP,还需要使用丙酮调节溶剂的挥发性和表面张力来制备均匀纤维结构的静电纺纤维膜。为了增强膜的整体抗润湿性,纤维结构的设计至关重要。在现有技术中,为了制作均匀纤维结构的模板印刷纤维膜,需要同时使用高沸点溶剂和低表面张力的非溶剂来调节溶液系统,但是非溶剂的加入增加了溶剂系统的挥发性,因此,在静电纺丝过程中,对环境温度和湿度的精确控制对于在膜表面形成图案至关重要。发明人发现高表面张力的溶液在静电纺丝过程中很难被电场力拉伸,有助于形成微球。集成的微球珠可以增加膜表面的粗糙度,最终增强膜的疏水性。将微球加入模板印刷的纤维膜中,可以显著增强其抗润湿和抗污染特性。因此,本发明在制备具有纹路结构和串珠结构的静电纺丝纤维只使用具有高沸点和高表面张力的溶剂,从而避免了非溶剂调节的需要,在整个静电纺丝过程中,无需对环境温度和湿度进行严格控制,从而简化了膜制备过程。本发明首次制备了具有微球珠结构的模板化PVDF-HFP静电纺丝膜(称为微球/模板化静电纺丝膜(EMs)),这是通过将PVDF-HFP溶解在N-甲基-2-吡咯烷酮(NMP)中实现的,NMP是一种具有高沸点和较高表面张力的溶剂。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118161987B_ABST
    Figure CN118161987B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of an anti-fouling super-hydrophobic membrane and application thereof in treating wastewater, and belongs to the field of membrane separation technology. In the electrospinning solution, a solvent with high boiling point and high surface tension is added, and a PVDF-HFP fiber matrix with a line structure and a string-bead structure is prepared through an electrospinning method. The PVDF-HFP fiber matrix is immersed in ethanol for phase conversion, water bath immersion and drying, and then an anti-fouling super-hydrophobic membrane is obtained. In the preparation of the electrospinning fiber with the line structure and the string-bead structure, only the solvent with the high boiling point and the high surface tension is used, so that the need for non-solvent adjustment is avoided. In the whole electrospinning process, the environment temperature and humidity do not need to be strictly controlled, so that the membrane preparation process is simplified.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of membrane separation technology, and particularly relates to a method for preparing an anti-fouling superhydrophobic membrane and its application in wastewater treatment. Background Technology

[0002] Membrane distillation (MD) is a novel membrane separation process that uses a hydrophobic microporous membrane as the separating medium and the vapor pressure difference across the membrane as the driving force for mass and heat transfer, combining membrane separation technology with distillation technology. In practice, a temperature difference is typically created across the membrane to form a gas-liquid interface on the surface of the hydrophobic membrane pores. This allows volatile substances to evaporate into vapor, which then passes through the membrane and condenses into distilled water on the other side, thus achieving separation. The performance of membrane distillation during the separation process depends on the membrane's properties; the membrane should meet requirements for excellent anti-wetting properties, high permeability, low thermal diffusivity, and durability.

[0003] Electrospun membranes (EMs) possess high porosity and high pore connectivity, which significantly reduce resistance to mass transfer and facilitate the smooth passage of water vapor through the membrane pores, thus achieving high permeate flux. Therefore, electrospun membranes have been widely used in membrane distillation applications in recent years. However, traditional electrospun membranes are typically composed of randomly interwoven nanofibers, a structure that makes the membrane exhibit a strong affinity for water molecules. This strong affinity allows water to easily permeate into the membrane's interior, thereby hindering the permeate movement of water vapor. During membrane distillation, the strong adhesion of water to the membrane significantly limits vapor transport efficiency. Furthermore, this strong water adhesion can lead to fouling deposition on the membrane surface, severely weakening the membrane's hydrophobic properties. As the membrane distillation separation process continues, this fouling deposition gradually wets the membrane pores, affecting the long-term separation performance and stability of membrane distillation.

[0004] To mitigate the strong water adhesion of EMs, several superhydrophobic membranes have been developed. One notable example is the superhydrophobic PDTS-ZnO-PVDF EMs designed by the team led by Jiahui Shao at Shanghai Jiao Tong University [Jun Li, Long-Fei Ren, Hong Susan Zhou, Jingren Yang, Jiahui Shao, Yiliang He. Fabrication of superhydrophobic PDTS-ZnO-PVDF membrane and its anti-wetting analysis in direct contact membrane distillation (DCMD) applications [J]. Journal of Membrane Science, 2021, 620: 118924]. This achievement involves incorporating perfluorodecyltriethoxysilane-fluorinated zinc oxide (ZnO) into the polyvinylidene fluoride membrane matrix. The resulting EMs exhibit a water contact angle (WCA) as high as 162.3° and a sliding angle (SA) as low as 9.8°, indicating excellent anti-wetting and sliding tendency. In direct contact membrane distillation (DCMD) treatment involving low surface tension sodium chloride / sodium dodecyl sulfate and calcium sulfate, this superhydrophobic membrane exhibits excellent antiwetting properties. However, this method requires the incorporation of nanoparticles to increase surface roughness, which presents challenges in controlling the distribution of nanoparticles on the membrane surface, thus limiting its practical application.

[0005] In our previous work [Lei Zhou, Haichao Zhang, Abdul Latif Ahmad, Soon Huat Tan, Siew Chun Low, Changlong Li. Hierarchical structure design of electrospunmembrane for enhanced membrane distillation treatment of shrimp aquaculture wastewater[J]. 2023, 306: 122591], we prepared superhydrophobic PVDF-HFP EMs using a template printing strategy, avoiding the need for additional nanoparticles and chemical treatment. Instead, we used a template to generate electrospun fiber membranes with patterned surfaces, endowing them with superhydrophobicity through a hierarchical micro / nano structure. A stainless steel mesh (SSM) with uniform microtexture served as a template for creating the textured structure on the EMs surface. The prepared membrane surface was able to trap a large amount of air, forming a solid / air / liquid composite interface and reducing the contact interface between the membrane and water. This facilitated the easy sliding of water droplets on the membrane surface, thereby removing contaminants adhering to the membrane surface. Therefore, the superhydrophobic membrane maintained stable performance throughout the membrane distillation separation process. However, creating microtextured structures on the surface of electrospun fiber membranes with uniform fiber structures, while introducing nanoscale roughness, requires precise control of the solvent-to-nonsolvent ratio and strict control of temperature and humidity during electrospinning, posing challenges to the simplicity of the preparation process. Furthermore, fiber membranes fabricated using only stencil printing technology exhibit superhydrophobic properties only on the membrane surface. Once the superhydrophobic surface is wetted, the feed solution easily penetrates into the membrane pores, causing the entire membrane to be rapidly wetted. Summary of the Invention

[0006] To address the aforementioned technical problems, this invention proposes a method for preparing an anti-scaling superhydrophobic membrane and its application in wastewater treatment.

[0007] To achieve the above objectives, the present invention provides the following technical solution:

[0008] A method for preparing an anti-scaling superhydrophobic membrane involves using stainless steel wire mesh (SSM) as a fiber collecting device, adding a solvent with a high boiling point and high surface tension to the electrospinning solution, preparing a PVDF-HFP fiber matrix by electrospinning, immersing the PVDF-HFP fiber matrix in ethanol for phase inversion, soaking in a water bath, and drying to obtain the anti-scaling superhydrophobic membrane.

[0009] Furthermore, the mesh size of the stainless steel wire mesh is between 100 and 400 meshes. For example, the mesh size of the stainless steel wire mesh can be 100, 200, 300, or 400 meshes, preferably 200 mesh. If the mesh is too small, the fibers (microspheres) cannot easily enter the mesh, making it difficult to form raised portions on the membrane surface; if the mesh is too large, the distance between the raised portions on the membrane surface is too large, reducing the air pockets under the membrane per unit area and decreasing the superhydrophobic effect.

[0010] Furthermore, the high-boiling-point and high-surface-tension solvent is N-methyl-2-pyrrolidone, dimethyl sulfoxide, or triethyl phosphate, preferably N-methyl-2-pyrrolidone. Such solvents are difficult to stretch by an electric field during electrospinning, which helps to form microspheres. The integrated microspheres can increase the surface roughness of the membrane, ultimately enhancing its hydrophobicity. Adding microspheres to the template-printed fiber membrane can significantly enhance its anti-wetting and anti-fouling properties. Therefore, this invention uses only solvents with high boiling points and high surface tension to prepare electrospun fibers with textured and beaded structures, thus avoiding the need for non-solvent conditioning. Throughout the electrospinning process, there is no need for strict control of ambient temperature and humidity, thereby simplifying the membrane preparation process.

[0011] Furthermore, the method for preparing the anti-fouling superhydrophobic membrane includes the following steps:

[0012] PVDF-HFP (polyvinylidene fluoride-hexafluoropropylene copolymer) was dissolved in N-methyl-2-pyrrolidone (NMP) and stirred until homogeneous to obtain a polymer solution.

[0013] Using the polymer solution as the electrospinning solution, electrospinning was performed to prepare PVDF-HFP fiber matrix;

[0014] The PVDF-HFP fiber matrix was immersed in ethanol for phase inversion, soaked in a water bath, and dried to obtain an anti-fouling superhydrophobic membrane.

[0015] Furthermore, the stirring temperature is 40°C, and the stirring time is 24 hours.

[0016] Furthermore, during electrospinning, the polymer solution delivery rate is 1.5 mL·h. -1 The applied voltage is 15kV, and the fiber collector is 15cm away from the needle tip.

[0017] Furthermore, the soaking time in the water bath is ≥2 hours.

[0018] Furthermore, the method for preparing the anti-fouling superhydrophobic membrane is as follows:

[0019] 15 wt.% PVDF-HFP (Sigma Aldrich) was dissolved in N-methyl-2-pyrrolidone (NMP, Sinopharm) and stirred at 40 °C for 24 h to obtain a polymer solution;

[0020] Electrospinning was performed using the polymer solution as the electrospinning solution at a rate of 1.5 mL·h. -1 The polymer solution was delivered at a rate of 15 kV, and a positive charge of 15 kV was applied to the metal needle tip (21 G). The fiber collector (200 mesh stainless steel mesh) was 15 cm away from the needle tip to prepare PVDF-HFP fiber matrix.

[0021] The PVDF-HFP fiber matrix was immersed in ethanol for phase inversion using a solvent-non-solvent exchange method, followed by water bath soaking for at least 2 hours to remove residual solvent. After drying, an anti-fouling superhydrophobic membrane was obtained. Testing showed that the electrospinning temperature was 20°C and the relative humidity (RH) was 50%, demonstrating that the process of this invention does not require strict temperature and humidity control (it should be noted that this refers only to the actual temperature and humidity recorded during electrospinning, as the experimental process requires parameter recording, not to the need for precise control under these parameters).

[0022] The present invention also provides an anti-fouling superhydrophobic membrane prepared by the above preparation method.

[0023] The present invention also provides the application of the above-mentioned anti-scaling superhydrophobic membrane in wastewater treatment.

[0024] Furthermore, the wastewater is aquaculture wastewater, such as shrimp farm wastewater.

[0025] Compared with the prior art, the present invention has the following advantages and technical effects:

[0026] In existing technologies, NMP has been reported as a solvent in the preparation of PVDF-HFP electrospun membranes. For example, patent application CN 105390646 A discloses a method for preparing composite membranes by electrospinning, where NMP can be the solvent and PVDF-HFP the fluorinated resin. However, this patent prepares a fiber membrane with a uniform fiber structure. Besides using NMP, this method also requires the use of acetone to adjust the volatility and surface tension of the solvent to prepare the electrospun fiber membrane with a uniform fiber structure. The design of the fiber structure is crucial to enhancing the overall anti-wetting properties of the membrane. In existing technologies, to create template-printed fiber membranes with a uniform fiber structure, both high-boiling-point solvents and low-surface-tension non-solvents are needed to adjust the solution system. However, the addition of non-solvents increases the volatility of the solvent system. Therefore, precise control of ambient temperature and humidity is essential for forming patterns on the membrane surface during electrospinning. The inventors discovered that solutions with high surface tension are difficult to stretch by an electric field during electrospinning, which helps to form microspheres. Integrated microspheres can increase the surface roughness of the membrane, ultimately enhancing its hydrophobicity. Adding microspheres to template-printed fiber membranes can significantly enhance their anti-wetting and anti-fouling properties. Therefore, this invention uses only solvents with high boiling points and high surface tension to prepare electrospun fibers with textured and beaded structures, thus avoiding the need for non-solvent conditioning. Throughout the electrospinning process, strict control of ambient temperature and humidity is unnecessary, simplifying the membrane preparation process. This invention is the first to prepare templated PVDF-HFP electrospun membranes with microsphere bead structures (referred to as microsphere / templated electrospun membranes (EMs)), achieved by dissolving PVDF-HFP in N-methyl-2-pyrrolidone (NMP), a solvent with high boiling points and high surface tension. Attached Figure Description

[0027] The accompanying drawings, which form part of this application, are used to provide a further understanding of this application. The illustrative embodiments and descriptions of this application are used to explain this application and do not constitute an undue limitation of this application. In the drawings:

[0028] Figure 1(A) is a SEM image of the surface morphology of SSM200 (200-mesh stainless steel wire mesh) in Example 1; (B) is a SEM image of the PVDF-HFP fiber matrix in Example 1 without solvent-to-nonsolvent exchange treatment; (C) is a low-magnification SEM image of the membrane surface (defined as the lower layer of microspheres / templated EMs) connected to the SSM collector after solvent-to-nonsolvent exchange treatment in Example 1; (D) is a high-magnification SEM image of the membrane surface (defined as the upper layer of microspheres / templated EMs) connected to the SSM collector after solvent-to-nonsolvent exchange treatment in Example 1; (E) is a SEM image of the membrane surface (defined as the upper layer of microspheres / templated EMs) in membrane-air interface contact after solvent-to-nonsolvent exchange treatment in Example 1; and (F) is a SEM image of the non-templated PVDF-HFP EMs in Comparative Example 1.

[0029] Figure 2 (A) shows the WCA and the frequency of water droplets passing through the bottom of the U-shaped surface; (B) is a schematic diagram of the water-membrane contact interface; (C) shows the WCA of microspheres / templated EMs after chemical and physical treatment.

[0030] Figure 3 (A) shows the pore size distribution of microsphere / templated EMs and non-templated PVDF-HFP EMs; (B) shows the thickness and porosity of microsphere / templated EMs and non-templated PVDF-HFP EMs.

[0031] Figure 4 Long-term DCMD separation performance of microsphere / templated EMs and non-templated PVDF-HFP EMs for treating shrimp farm wastewater;

[0032] Figure 5 SEM and EDX results for ((A), (B)) untemplated PVDF-HFP EMs and ((C), (D)) microsphere / templated EMs after DCMD separation (running for 72 hours);

[0033] Figure 6 SEM images of (A) untemplateable PVDF-HFP EMs and (B) microsphere / templateable EMs after DCMD separation (running for 72 hours). Detailed Implementation

[0034] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0035] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0036] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0037] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be readily apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0038] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0039] All raw materials used in the embodiments of this invention were obtained through commercial purchase.

[0040] This invention provides a method for preparing an anti-scaling superhydrophobic membrane. Using stainless steel wire mesh (SSM) as a fiber collecting device, a high-boiling-point and high-surface-tension solvent is added to the electrospinning solution to prepare a PVDF-HFP fiber matrix via electrospinning. The PVDF-HFP fiber matrix is ​​then immersed in ethanol for phase inversion, followed by water bath soaking and drying to obtain the anti-scaling superhydrophobic membrane. The high-boiling-point and high-surface-tension solvent is N-methyl-2-pyrrolidone, dimethyl sulfoxide, or triethyl phosphate, preferably N-methyl-2-pyrrolidone.

[0041] The characterization methods for the membranes prepared in Example 1 and Comparative Example 1 of this invention are as follows:

[0042] The morphological properties of the films in Example 1 and Comparative Example 1 were observed using a field emission scanning electron microscope (FESEM, Hitachi S-4800, Japan) to study their surface structure in detail. Water contact angle (WCA) measurements were performed using a contact angle meter (ZC705, Dongguan Zhicheng, China). During the measurement, a 3 μL droplet of deionized water was carefully added to the surface of the sample (i.e., the film of Example 1 or Comparative Example 1, hereinafter the same) using a syringe, followed by photographing. Then, the WCA value was determined based on the droplet profile using image analysis software.

[0043] The pore size distribution was determined using a capillary flow porosimeter (POROLUX 1000, Germany). Before testing, the samples underwent pretreatment with a low surface tension wetting liquid, specifically by immersing them in a perfluoroether solvent (surface tension 16 dyne / cm) for 15 minutes. The flow rates under wet and dry conditions were measured using nitrogen gas to determine the average pore size and its distribution. The membrane thickness was measured using a digital micrometer, and the average of five measurements at different locations was taken. The membrane porosity was calculated using a gravimetric method.

[0044] Following DCMD, the contaminated membrane underwent comprehensive analysis to investigate its surface structure, elemental composition, and chemical composition. This analysis was performed using a field emission scanning electron microscope (Hitachi FESEM-EDX-4800 model) equipped with energy-dispersive X-ray spectroscopy (EDX). Furthermore, a comprehensive chemical composition analysis of the contaminated membrane was conducted using a Thermo Scientific Nicolet iS20 Fourier transform infrared spectroscopy (FTIR) instrument to gain a deeper understanding of its properties.

[0045] The technical solution of the present invention will be further illustrated by the following embodiments.

[0046] Example 1: Preparation of Microsphere / Template-based Electrospun Membranes (EMs)

[0047] 15 wt.% PVDF-HFP (Sigma Aldrich) was dissolved in N-methyl-2-pyrrolidone (NMP, Sinopharm) and stirred at 40 °C for 24 h to obtain a polymer solution;

[0048] Using the above polymer solution as the electrospinning solution, electrospinning was performed at a rate of 1.5 mL·h. -1 The polymer solution was delivered at a rate of 15 kV, and a positive charge of 15 kV was applied to the metal needle tip (21 G). The fiber collector (200 mesh stainless steel mesh) was 15 cm away from the needle tip to prepare PVDF-HFP fiber matrix.

[0049] The PVDF-HFP fiber matrix was immersed in ethanol for phase inversion using a solvent-non-solvent exchange method. After soaking in a water bath for 2 hours to remove residual solvent, it was dried in air to obtain an anti-fouling superhydrophobic membrane (i.e., microsphere / template electrospun membrane (EMs)), which will be referred to as microsphere / template EMs from now on.

[0050] Example 2

[0051] 18 wt.% PVDF-HFP (Sigma Aldrich) was dissolved in dimethyl sulfoxide (NMP, Sinopharm) and stirred at 50 °C for 24 h to obtain a polymer solution;

[0052] Using the above polymer solution as the electrospinning solution, electrospinning was performed at a rate of 1.5 mL·h. -1 The polymer solution was delivered at a rate of 15 kV, and a positive charge of 15 kV was applied to the metal needle tip (21 G). The fiber collector (100 mesh stainless steel mesh) was 15 cm away from the needle tip to prepare the PVDF-HFP fiber matrix.

[0053] The PVDF-HFP fiber matrix was immersed in ethanol for phase inversion using a solvent-non-solvent exchange method, then soaked in a water bath for 2 hours to remove residual solvent, and finally dried in air to obtain an anti-fouling superhydrophobic membrane.

[0054] Example 3

[0055] 21 wt.% PVDF-HFP (Sigma Aldrich) was dissolved in triethyl phosphate (NMP, Sinopharm) and stirred at 60 °C for 24 h to obtain a polymer solution;

[0056] Using the above polymer solution as the electrospinning solution, electrospinning was performed at a rate of 1.5 mL·h. -1 The polymer solution was delivered at a rate of 15 kV, and a positive charge of 15 kV was applied to the metal needle tip (21 G). The fiber collector (400 mesh stainless steel mesh) was 15 cm away from the needle tip to prepare PVDF-HFP fiber matrix.

[0057] The PVDF-HFP fiber matrix was immersed in ethanol for phase inversion using a solvent-non-solvent exchange method, then soaked in a water bath for 2 hours to remove residual solvent, and finally dried in air to obtain an anti-fouling superhydrophobic membrane.

[0058] Comparative Example 1: Preparation of untemplated PVDF-HFP EMs

[0059] 15 wt.% PVDF-HFP (Sigma Aldrich) was dissolved in N,N'-dimethylformamide / acetone (DMF / AC, weight ratio 1:1, Merck) and stirred at 40 °C for 24 h to obtain a polymer solution.

[0060] Using the above polymer solution as the electrospinning solution, electrospinning was performed at a flow rate of 1.0 mL·h. -1 The polymer solution was delivered at a rate of 15 kV with a metal needle tip (21G) and a fiber collector (aluminum foil) 15 cm away from the needle tip to prepare a PVDF-HFP fiber matrix.

[0061] The PVDF-HFP fiber matrix was immersed in ethanol for phase inversion using a solvent-non-solvent exchange method, then soaked in a water bath for 2 hours to remove residual solvent, and finally dried in air to obtain a hydrophobic membrane (i.e., non-templateable PVDF-HFP EMs).

[0062] This invention proposes a simple one-step electrospinning method for preparing microsphere / templated EMs with textured and beaded structures. By introducing microsphere structures into the membrane, this invention not only improves its overall anti-wetting effect but also increases the surface roughness of the membrane, thereby enhancing its antifouling ability. This invention provides a comprehensive evaluation of microsphere / templated electrospun membranes (EMs) with complex microstructures, particularly assessing their water flux, desalination efficiency, and anti-scaling ability in practical wastewater treatment applications using direct contact membrane distillation (DCMD) (illustrated using the microsphere / templated EMs of Example 1 and the non-templated PVDF-HFP EMs of Comparative Example 1).

[0063] Figure 1 (A) shows the morphology of the SSM collector, which is made of metal warp and weft threads woven in a twill pattern, giving it a uniform uneven microstructure. Figure 1 Image (B) depicts the structure of the membrane surface connected to the SSM collector, where the fiber matrix exhibits a patterned structure, indicating successful surface printing via SSM. When the electrospun fibers come into contact with the SSM surface, they adhere to it and conform to its wavy texture. As the solvent in the nanofibers evaporates, they solidify to form a mirror surface corresponding to the template geometry. Fibers within the hollow regions of the SSM protrude from the membrane surface, thus creating imprints of the SSM texture on the membrane surface.

[0064] The results show that patterned fiber membranes can be easily prepared using the high-boiling-point (203℃) solvent NMP during electrospinning without strict temperature and humidity restrictions. However, the fibers on the SSM collector exhibit a tendency to aggregate, forming a dense felt layer. This phenomenon is caused by the slow evaporation rate of the high-boiling-point solvent, leading to partial dissolution of the fiber felt. This low-porosity membrane results in increased water vapor mass transfer resistance, making it unsuitable for DCMD.

[0065] This invention employs a solvent-non-solvent exchange method to improve membrane porosity. To evaluate the impact of solvent exchange on the microtexture structure of the printed membrane, low-magnification SEM images of both sides of the microspheres / templated EMs were analyzed. Figure 1 As shown in (C), the membrane surface attached to the SSM collector exhibits a layered, rough microtexture. The microtexture of raised areas (outlined by white dashed circles) and grooves (outlined by black dashed circles) is retained on the microspheres / templated EMs, indicating that the solvent replacement process has no effect on the patterned structure. Furthermore, because solvent replacement rapidly removes residual solvent from the fibers, and non-solvent-induced phase separation leads to rapid fiber solidification, the fibers do not adhere together. High-magnification SEM image analysis was performed on both sides of the microspheres / templated EMs, as shown in Figure C. Figure 1 As shown in (D), microsphere structures are formed along the nanofibers. The appearance of microspheres on the nanofibers is mainly due to the use of a solution with high surface tension. Here, NMP is used as the solvent, with a surface tension of 40 mN·m. -1 In this case, the electrostatic force is insufficient to overcome the surface tension of the solution, causing the stretched liquid to form spherical droplets. Therefore, the ability of NMP to generate microspheres on the surface of nanofibers has been demonstrated. Compared to fibers, the average diameter of the microspheres (4.50 μm) is almost 14 times that of the fiber diameter (318 nm). Interestingly, both the microspheres and fibers exhibit rough surfaces. Figure 1 (Image on the right, D). This roughness originates from non-solvent-induced phase separation. During solvent exchange to remove residual NMP, the uneven solidification rate inside and outside the microspheres and fibers leads to surface shrinkage and roughness. These rough structures impart nanoscale roughness to the membrane surface.

[0066] However, in comparison Figure 1 In the middle (E) view of the membrane surface facing the membrane-air interface (i.e., the upper layer of the membrane), it is evident that the untemplated membrane-air interface does not replicate the simulated structure as clearly as the membrane surface facing the SSM collector. This difference stems from the electrospinning process, in which nanofibers are assembled layer by layer onto the top collector, forming a nanofiber mat of a certain thickness over time. As the membrane thickness increases, the electrospun nanofibers are further away from the SSM surface, thus limiting the formation of raised textures that can mimic the SSM structure. This indicates that the creation of patterned structures on the membrane surface can impart higher roughness, thereby enhancing the membrane's resistance to wetting. Although in Figure 1 No structure mimicking SSM was observed in (E), but the large microspheres formed on the membrane surface may still generate high roughness, thereby establishing uniform roughness and enhancing the overall anti-wetting ability and durability of the membrane.

[0067] This invention prepared a control nanofiber membrane, namely untemplated PVDF-HFP EMs (Comparative Example 1), which was prepared by electrospinning a mixture of PVDF-HFP with DMF and AC solvents at a 1:1 mass ratio. Both solvents have low boiling points and low surface tension. This serves as a reference to compare microsphere / templated EMs incorporating microbeads. Example 1 was developed using NMP, a solvent with a high boiling point. Figure 1 As shown in Figure (F), the untemplated PVDF-HFP EMs exhibit a uniform and smooth fibrous structure. The low roughness observed in this structure implies weak resistance to wetting during membrane distillation. To verify this hypothesis, subsequent sections will delve into the wetting properties of untemplated PVDF-HFP EMs and microsphere / templated electrospun membranes (microsphere / templated EMs).

[0068] In membrane distillation, membranes with excellent water-repellent properties can effectively enhance their anti-wetting ability. Membrane wettability can be characterized by the water contact angle (WCA). Figure 2 As shown in (A), the water contact angle of the untemplated PVDF-HFP EMs is relatively low at 138°. In contrast, the upper layer of the microsphere / templated EMs exhibits superhydrophobic behavior with a water contact angle as high as 151°, exceeding the superhydrophobic threshold (WCA>150°). The microspheres on the nanofiber surface increase the roughness of the membrane, thereby enhancing its hydrophobicity, a highly desirable property in membrane distillation processes as it improves the membrane's anti-wetting and durability. Interestingly, the water contact angle on the surface facing the SSM substrate is even higher, reaching 157°. This can be attributed to the surface printing process using SSM, which creates protrusions and grooves mimicking the SSM structure, further increasing the membrane's roughness. Consequently, these grooves reduce the contact area between the membrane and the feed liquid, resulting in a higher water contact angle.

[0069] Superhydrophobicity of a membrane is a key indicator for evaluating its antiwetting performance, and is generally associated with higher antiwetting ability. To quantitatively analyze the superhydrophobic properties of the membrane, the dynamic behavior of approximately 50 μL droplets on the membrane surface was monitored in a U-shaped channel. A higher frequency of droplet passage through the bottom of the membrane indicates better superhydrophobic sliding properties on the membrane surface. Figure 2 As shown in (A), water droplets adhered directly to the surface of untemplated PVDF-HFP EMs, while water droplets traversed the top and bottom of microsphere / templated EMs 2 and 5 times, respectively. The smooth fibers of untemplated PVDF-HFP EMs lacked sufficient roughness to accommodate air pockets, resulting in continuous interaction between liquid and solid across the entire membrane surface. Therefore, the adhesion of water to the fibers hindered smooth sliding.

[0070] like Figure 2As shown in (B), the microspheres exert a weak anchoring effect on the water droplets, causing the interaction between the liquid and solid surfaces to become discontinuous. This allows the water droplets to remain in a metastable state on top of the microspheres, enabling them to slide easily with almost no hysteresis. Compared to the top layer of the microsphere / templated EMs, the bottom layer exhibits lower water adhesion due to the increased surface roughness from the bottom printing. The reduced contact area between the microspheres and the water droplets, along with the enhanced presence of air pockets, further exacerbates the loose anchoring effect, resulting in a higher water sliding effect. Therefore, the synergistic effect of the microspheres and SSM surface printing holds promise for improving the overall wettability of the membrane.

[0071] The durability of the printed microtextured structure was evaluated by testing the wetted carbon matrix (WCA) of the chemically and physically treated microspheres / templated EMs. Specifically, its resistance to acid and alkaline environments was verified by immersing the film in HCl solution (0.01 mol / L) and NaOH solution (0.01 mol / L), while its thermal and mechanical stability were tested by heat treatment at 100 °C and ultrasonic treatment at 40 Hz for one hour, respectively. Figure 2 As shown in (C), the WCA of the membrane surface (156.5°, 156.1°, 155.1°, and 155.6°, respectively) remained almost unchanged compared to the original state before treatment, indicating that the printed microtexture structure has excellent stability. Therefore, microspheres / templated EMs prepared by SSM template printing technology have great potential in improving membrane anti-wetting and durability, thus promising to enhance membrane distillation performance.

[0072] The pore structure of the membrane has a significant impact on the vapor flux in membrane distillation. Generally, larger pore sizes and higher porosity enhance vapor transport by reducing mass transfer resistance over a larger surface area. Before performing DCMD testing, porosity and pore size analyses were performed on untemplated PVDF-HFP EMs and microsphere / templated EMs, and the results are as follows: Figure 3 As shown. In Figure 3 In (A), the untemplated PVDF-HFP EMs have an average pore size of 1.25 μm, while the microsphere / templated EMs exhibit a smaller average pore size of 0.93 μm due to the microspheres occupying the voids between the intersecting nanofibers. Despite the reduced pore size, the smaller pore size contributes to increased liquid inlet pressure. Figure 3In (B), the porosities of untemplated PVDF-HFP EMs and microsphere / templated EMs were 88.1% and 59.3%, respectively. The reduced porosity of the microsphere / templated EMs compared to the untemplated PVDF-HFP EMs is attributed to the microspheres occupying interstitial spaces. While the reduced porosity may affect low-flux membrane distillation operations, the superhydrophobicity and relatively large pore openings (close to 1 μm) mitigate the vapor transport limitations caused by porosity. Further performance testing of the membranes in DCMD will explore the independent and synergistic effects of these membrane properties.

[0073] To evaluate the long-term stability and antifouling performance of microsphere / templated EMs in DCMD separation, actual aquaculture wastewater (shrimp farm wastewater) was used, and the membrane was compared with non-templated PVDF-HFP EMs. Figure 4 Results of continuous 72-hour DCMD separation are presented, including water vapor permeation flux and salt rejection. An initial water vapor permeation rate of 25.45 kg·m³ was observed in the untemplated PVDF-HFPEMs. -2 ·h -1 The initial permeation rate of the microspheres / templated EMs was 32.68 kg·m³. -2 ·h -1 Although the pore size and porosity of microsphere / templated EMs are smaller compared to non-templated PVDF-HFP EMs, their initial permeation flux is higher. The higher initial water vapor permeation flux of microsphere / templated EMs can be attributed to their superhydrophobicity, which prevents water droplets from adhering to the membrane surface and maintains a larger active space for water vapor permeation.

[0074] To verify the accumulation of contaminants on the membrane surface, the surface structure of untemplated PVDF-HFP EMs and microsphere / templated EMs was observed using scanning electron microscopy (SEM) after the DCMD process. Figure 5 These SEM images are shown. For example... Figure 5 As shown in Figure (A), the surface of untemplated PVDF-HFP EMs is covered with a thick layer of inorganic deposits, which clog the membrane pores and reduce permeation flux. Untemplated PVDF-HFP EMs exhibit strong water affinity, leading to the formation of a quiescent water layer near the membrane, which in turn promotes the nucleation and growth of inorganic salts. Conversely, as... Figure 5As shown in (C), the surface of the microsphere / templated EMs exhibits almost no fouling. This is because the membrane's high superhydrophobicity hinders the formation of heterogeneous nuclei. The microsphere / templated EMs maintain an effective evaporation surface, allowing water vapor to pass through the membrane efficiently, with only a small amount of nanofibers covered by fouling. Therefore, the permeate flux of the microsphere / templated EMs remains stable, with only a slight decrease. These results support the superior antifouling ability of microsphere / templated EMs compared to non-templated PVDF-HFP EMs, making them a promising candidate material for long-term DCMD separation of shrimp farm wastewater.

[0075] The surface elemental contents of untemplated PVDF-HFP EMs and microsphere / templated EMs were determined by EDX analysis, and the results are as follows: Figure 5 As shown in (B) and (D). The analysis results show that, except for carbon and fluorine, all other recognized components on the untemplated membrane were significantly higher, indicating that the membrane surface was covered with a large amount of organic contaminants. Conversely, the microsphere / templated EMs had higher carbon and fluorine contents, while the contents of other elements were lower, indicating that inorganic fouling deposits adhered less to the surface of the microsphere / templated EMs membrane. These results are consistent with... Figure 5 The observations in (A) and (C) are consistent, namely that the surface of the untemplated membrane is covered with a thick layer of inorganic deposits, while the surface of the microsphere / templated EMs has very little deposit.

[0076] In addition to inorganic pollutants, shrimp farm wastewater also contains various organic pollutants. These organic pollutants mainly include humic acid, proteins, polysaccharides, and oils. To study the surface morphology of organic pollutant layers on untemplated PVDF-HFP EMs and microsphere / templated EMs, the following methods were employed: Figure 6 The study shown.

[0077] like Figure 6 As shown in (B), the surface of the microspheres / templated EMs shows almost no organic contaminant adhesion, only a slight gel-like coating. Conversely, as... Figure 6 As shown in (A), the surface of the PVDF-HFP NM is completely covered by a dense gel-like material. This finding indicates that superhydrophobic microspheres / templated EMs possess significant resistance to organic contaminant adsorption. This is because the microstructure on the surface of the microspheres / templated EMs can induce turbulence and increase the shear rate of the membrane surface during DCMD, thereby reducing contaminant deposition. Furthermore, larger microspheres form a rougher microstructure, leading to increased turbulence intensity of the feed water flow, which further reduces contaminant adhesion to the membrane surface. Therefore, very little organic contaminant accumulates on the surface of the microspheres / templated EMs.

[0078] These results further confirm the superior antifouling performance of microsphere / templated EMs. Their unique microstructure not only effectively resists the adhesion of inorganic fouling substances but also significantly reduces the accumulation of organic pollutants. This gives microsphere / templated EMs a significant advantage in treating complex wastewater systems such as shrimp farm wastewater, and they hold promise as a highly efficient and stable membrane material option for the wastewater treatment field.

[0079] The above are merely preferred embodiments of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.

Claims

1. The application of an anti-fouling superhydrophobic membrane in direct contact membrane distillation treatment of wastewater, characterized in that, The wastewater is aquaculture wastewater; The method for preparing the anti-scaling superhydrophobic membrane involves using a stainless steel wire mesh as a fiber collecting device, adding a solvent with a high boiling point and high surface tension to the electrospinning solution, preparing a PVDF-HFP fiber matrix by electrospinning, immersing the PVDF-HFP fiber matrix in ethanol for phase inversion, soaking in a water bath, and drying to obtain the anti-scaling superhydrophobic membrane. The solvent with high boiling point and high surface tension is N-methyl-2-pyrrolidone, dimethyl sulfoxide, or triethyl phosphate; During electrospinning, the polymer solution delivery rate is 1.5 mL·h. -1 The applied voltage is 15 kV, and the fiber collector is 15 cm away from the needle tip; The soaking time in the water bath is ≥2 hours; Throughout the electrospinning process, there is no need for strict control of ambient temperature and humidity; The stainless steel wire mesh is made of metal warp and weft threads interwoven in a twill weave, and has a uniform uneven microstructure.

2. The application according to claim 1, characterized in that, The stainless steel wire mesh has a mesh size of 100 to 400 mesh.

3. The application according to claim 1, characterized in that, The method for preparing the anti-fouling superhydrophobic membrane includes the following steps: PVDF-HFP was dissolved in N-methyl-2-pyrrolidone and stirred until homogeneous to obtain a polymer mass fraction of 15%~21%; Using the polymer solution as the electrospinning solution, electrospinning was performed to prepare PVDF-HFP fiber matrix; The PVDF-HFP fiber matrix was immersed in ethanol for phase inversion, soaked in a water bath, and dried to obtain an anti-fouling superhydrophobic membrane.

4. The application according to claim 3, characterized in that, The stirring temperature is 40℃~60℃, and the stirring time is 24h.

Citation Information

Patent Citations

  • Homogeneous fiber reinforced fluorine-containing resin based diaphragm

    CN105390646A

  • High polymer material, super-hydrophobic porous membrane, coating, preparation method and applications

    CN110548417A